A brief period of intensive cardiac rehabilitation improves global longitudinal strain and diastolic function after a first uncomplicated myocardial infarction. Issue 3 (4th May 2017) - Malfatto, Gabriella; Revera, Miriam; Branzi, Giovanna; Ciambellotti, Francesca; Giglio, Alessia; Blengino, Simonetta; Oldani, Matteo; Facchini, Camilla; Parati, Gianfranco; Facchini, Mario
Abstract : Objectives In patients with abnormal left ventricular ejection fraction (LVEF) after acute myocardial infarction (AMI), cardiac rehabilitation with physical training prevents cardiac remodelling. To define the role of rehabilitation in the recovery of ventricular function in less severe cases, we studied its effects on more refined indexes of left ventricular function in uncomplicated, low-risk patients. Methods and results Fifty-five patients underwent percutaneous coronary revascularization after uncomplicated first AMI. Thirty-four started cardiac rehabilitation with counselling and physical training; 21 patients did not train, followed a counselling program and were taken as controls. Echocardiography was performed at baseline, after rehabilitation or counselling program and at six months follow-up. We measured: global strain (GS%) with speckle tracking analysis, E/e' by tissue Doppler imaging (TDI), left ventricular elastance (KLV ) from the deceleration time (DT), LVEF, systolic and diastolic volumes, wall motion score index (WMSI). At baseline, groups had similar GS%, KLV, LVEF, DT, E/e', systolic and diastolic volumes, WMSI. Rehabilitation increased peak VO2 by 18% ( P <  0.05) and improved GS%, KLV, LVEF, E/e' and WMSI ( P <  0.02) that were unchanged in controls. The improvement persisted at six months. Conclusions After a first uncomplicated AMI, abnormalities of left systolic and diastolic ventricular function may be present persisting over time despite a normal LVEF, which are fully reverted by cardiac rehabilitation.